2013
DOI: 10.1088/0957-4484/24/11/115501
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical current-sensing atomic force microscopy in conductive solutions

Abstract: Abstract. Insulated atomic force microscopy probes carrying gold conductive tips were fabricated and employed as bifunctional force and current sensors in electrolyte solutions under electrochemical potential control. The application of the probes for current-sensing imaging, force and current-distance spectroscopy as well as scanning electrochemical microscopy experiments was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…In this work, we carried out CSAFM experiments334142 in solution and evaluated conductances and breaking forces at the different stages of elongation of Au-molecule(s)-Au junctions formed by symmetric tolane-type molecules (Figure 1) with two pyridyl (1,2-di(pyridin-4-yl)ethyne, PY2), dihydrobenzothiophene (1,2-bis(2,3-dihydrobenzo[ b ]thiophen-5-yl)ethyne, BT2), amine (4,4′-(ethyne-1,2-diyl)dianiline, NH 2 2), nitrile (4,4′-(ethyne-1,2-diyl)dibenzonitrile, CN2), and thiol (4,4′-(ethyne-1,2-diyl)dibenzenethiol, SH2) anchoring groups. Their conductance was recently characterised in STMBJ and MCBJ experiments2022.…”
mentioning
confidence: 99%
“…In this work, we carried out CSAFM experiments334142 in solution and evaluated conductances and breaking forces at the different stages of elongation of Au-molecule(s)-Au junctions formed by symmetric tolane-type molecules (Figure 1) with two pyridyl (1,2-di(pyridin-4-yl)ethyne, PY2), dihydrobenzothiophene (1,2-bis(2,3-dihydrobenzo[ b ]thiophen-5-yl)ethyne, BT2), amine (4,4′-(ethyne-1,2-diyl)dianiline, NH 2 2), nitrile (4,4′-(ethyne-1,2-diyl)dibenzonitrile, CN2), and thiol (4,4′-(ethyne-1,2-diyl)dibenzenethiol, SH2) anchoring groups. Their conductance was recently characterised in STMBJ and MCBJ experiments2022.…”
mentioning
confidence: 99%
“…The topographical images generated using this type of probe typically have an exceptional lateral resolution owing to their highly sharpened imaging point. Wandlowski et al demonstrated the "current sensing" application of such probes at a gold band substrate, 54 although in this case the probe electrode was contacted to the surface throughout the entire experiment, such that the current measurement reected electron transfer taking place across the entire gold band structures rather than processes localised to the tip apex alone. current contrast, signal-to-noise) using such probes, and other variants, 34 have also been generally quite high although this in part relates to the relatively large electrode size (typically several hundred nm), which leads to large ($10 nA) currents and ultimately limits the spatial resolution of current mapping to the mm domain.…”
Section: Afm Positioningmentioning
confidence: 99%
“…Direct visualization of the electronic conductivity evolutions on different crystal faces enable better understanding the origin of polarization-dependent battery performance. Recently, new techniques have been developed to allow the Atomic Force Microscopy (AFM) to be operated in liquid conditions [14][15][16][17], which can image the cathode materials at charging and discharging processes [18,19], thus providing the capability to directly probe the physical-chemical properties of the liquid/solid interface. Here we employed the in situ current-sensing Atomic Force Microscopy (CSAFM) to study the interfacial conductivity on the surface of LCO crystal grains and to probe the IMT on a certain crystal face.…”
Section: Introductionmentioning
confidence: 99%